ANALISIS KINERJA KEUANGAN DAN FIRM SIZE DALAM MENENTUKAN KEPUTUSAN HEDGING (Studi Kasus Pada Perusahaan Sektor Basic Material yang Terdaftar di Bursa Efek Indonesia) - Maghfirah Nur Fadilah, (2022)
Export and import activities are part of international trade. Export activities are led by the industrial sector while imports are led by raw material support. International trade carries a risk of movement in foreign exchange rates which can be minimized through hedging. This reason is the basis for examining the effect of financial performance and firm size on hedging decisions in basic material sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. A total of 52 companies have been selected using purposive sampling as the sample in the study. Tests were carried out with logistic regression analysis through EViews 12. The results obtained are that liquidity has a negative effect and firm size has a significant positive effect on hedging decisions. Meanwhile, profitability and leverage have no significant effect on hedging decisions